An overview of the European standard clinical practice recommendations for choroid plexus tumours - David King; Brigitte Bison; Ofelia Cruz; Claudia C. Faria; Iwona Filipek; Jonathan L. Finlay; Miklós Garami; Uwe R. Kordes; Ulrike Löbel; Jilly Maclean; Torben Stamm Mikkelsen; Denise Obrecht-Sturm; et al. (EJC Paediatric Oncology)
Choroid plexus tumours (CPT) are rare epithelial brain tumours that primarily affect very young children. They can be classified as benign choroid plexus papilloma (CPP, WHO grade 1), intermediate grade atypical choroid plexus papilloma (aCPP, WHO grade 2) or highly malignant choroid plexus carcinoma (CPC, WHO grade 3). Treatment is dependent on tumour grade, surgical resection, the age of the child and somatic and germline TP53 mutational status. CPP and aCPP have a good prognosis and are frequently curable with surgery alone. In contrast, the prognosis in CPC is often poor, despite intensive multimodal treatment with surgery, chemotherapy and radiotherapy. Management is complicated by the increased incidence of germline TP53 mutations and cancer predisposition (Li-Fraumeni syndrome), especially in CPC, whilst the rarity of the diagnosis means there are a lack of robust clinical data on which to base treatment decisions. Studies generally comprise of retrospective, single arm and centre trials or case series, and patient numbers are small leading to conflicting results that are difficult to interpret. Standardised treatment protocols have historically been lacking.The aim of this document is to provide a reference standard for the treatment of CPT on behalf of the European Society for Paediatric Oncology (SIOPE). We review the previously published literature and provide consensus key recommendations for the management of CPP, aCPP and CPC including surgical approaches and when appropriate, the role of chemotherapy and radiotherapy. Suggested follow-up and possible relapse strategies are also suggested.